All Incontinence is Not Created Equal: Impact of Urinary and Fecal Incontinence on Quality of Life in Adults with Spina Bifida - Szymanski, Konrad M; Cain, Mark P; Whittam, Benjamin; Kaefer, Martin; Rink, Richard C; Misseri, Rosalia (The Journal of urology, 2017)
Purpose We previously reported that the self-reported amount of urinary incontinence is the main predictor of lower health related quality of life in adults with spina bifida. In this study we sought to determine the impact of fecal incontinence on health related quality of life after correcting for urinary incontinence. Materials and Methods An international sample of adults with spina bifida was surveyed online in 2013 to 2014. We evaluated fecal incontinence in the last 4 weeks using clean intervals (less than 1 day, 1 to 6 days, 1 week or longer, or no fecal incontinence), amount (a lot, medium, a little or none), number of protective undergarments worn daily and similar variables for urinary incontinence. Validated instruments were used, including QUALAS-A (Quality of Life Assessment in Spina bifida for Adults) for spina bifida specific health related quality of life and the generic WHOQOL-BREF (WHO Quality of Life, short form). Linear regression was used (all outcomes 0 to 100). Results Mean age of the 518 participants was 32 years and 33.0% were male. Overall, 55.4% of participants had fecal incontinence, 76.3% had urinary incontinence and 46.9% had both types. On multivariate analysis fecal incontinence was associated with lower bowel and bladder health related quality of life across all amounts (−16.2 for a lot, −20.9 for medium and −18.5 for little vs none, p <0.0001) but clean intervals were not significant (−4.0 to −3.4, p ≥0.18). Conversely, health related quality of life was lower with increased amounts of urinary incontinence (−27.6 for a lot, −18.3 for medium and −13.4 for little vs none, p <0.0001). Dry intervals less than 4 hours were not associated with lower health related quality of life (−4.6, p = 0.053) but the use of undergarments was associated with it (−7.5 to −7.4, p ≤0.01). Fecal incontinence and urinary incontinence were associated with lower WHOQOL-BREF scores. Conclusions Fecal incontinence and urinary incontinence are independent predictors of lower health related quality of life in adults with spina bifida. Health related quality of life is lower with an increasing amount of urinary incontinence. Fecal incontinence has a more uniform impact on health related quality of life regardless of frequency or amount.